PERTANGGUNGJAWABAN PIDANA BAGI PSIKOPAT - Saputri, Evi Nur; Soeskandi, Hari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of this research is to find answers and legal certainty related to criminal responsibility for someone who is said to be a psychopath and also to seek legal certainty whether a psychopath can be sentenced to criminal penalties using Article 338 of the Criminal Code. The researcher uses this type of normative legal research which aims to find the rule of law, legal principles, and actual legal doctrines in order to provide answers and solve a problem on the legal issue being studied. By using the concept that the researcher has created, and the researcher wants to explain the criminal liability for a psychopath who has committed a crime of murder, and determine which legal rules are appropriate and can be imposed on a psychopath, as well as explain that a psychopath is different from someone who has a mental disorder. mental, so that it can be used as a reference or comparison for the imposition of criminal penalties. And also looking for answers, he can see a person suffering from a psychopathic disorder from various public views to provide legal certainty. So that it can provide answers and references for the wider community regarding criminal liability against a psychopath